Aproximación al fenómeno de las apuestas deportivas desde una óptica sociológica y econométrica. análisis de escenarios prospectivos del sector y modelos fácticos de inversión del capital en las plataformas de apuestas online (2023)
This document carries out a conjunctural analysis of the environment in the world of sports betting, this being a sector that has shown exponential growth in recent years on a global scale as a result of technological massification and the consolidation of sports and games of chance. . The work seeks to carry out a factual recognition of the procedural environment that surrounds the world of betting, for this purpose regulatory sections, intervention strategies from a psychological perspective and empirical explanations are contextualized with respect to the economic context that an investment decision entails. From the methodological point of view, the work presents a qualitative research model addressing an experimental exploratory scenario, and incorporating correlational-based elements from a transversal perspective through primary and secondary information tools, thereby seeking to recognize the subject matter of study, and understand the implication of the phenomenon of sports betting from a sociological and econometric notion. The article recognizes probabilistic models in relation to sports betting, and the rational behavior involved in betting from a rational perspective, in addition to recognizing the relevance of capital management processes to understand the behavioral economics behind of an economic decision; The findings of the study provide a visualization of the investment criteria in the world of online betting, for this the position of a bettor is individualized and this information is contrasted with parametric data used for capital management in a virtual betting house.